2010
DOI: 10.1073/pnas.1004741107
|View full text |Cite
|
Sign up to set email alerts
|

Activated factor V is a cofactor for the activation of factor XI by thrombin in plasma

Abstract: The mechanism by which the intrinsic pathway of coagulation contributes to physiological hemostasis is enigmatic. Thrombin activates factor XI, a key zymogen in this pathway, which leads to increased thrombin generation. As thrombin-dependent activation of factor XI in vitro is relatively inefficient, we hypothesized that a physiological cofactor supports this reaction in a plasma environment. We therefore investigated whether the cofactors of coagulation, activated factor V, activated factor VIII, high-molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…Although multiple studies have reported the activation of FXI by thrombin using purified proteins, [8][9][10][11][12] some have questioned whether this reaction can proceed to any significant extent in plasma. [13][14][15] Figure 2.…”
Section: Polyp Can Accelerate Clotting Of Plasma and Enhance Thrombinmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple studies have reported the activation of FXI by thrombin using purified proteins, [8][9][10][11][12] some have questioned whether this reaction can proceed to any significant extent in plasma. [13][14][15] Figure 2.…”
Section: Polyp Can Accelerate Clotting Of Plasma and Enhance Thrombinmentioning
confidence: 99%
“…A solution to this conundrum was proposed in 1991 by Naito and Fujikawa 8 and by Gailani and Broze,9 who reported that thrombin up-regulates its own generation by feeding back to activate FXI, leading to a "revised model of coagulation." [9][10][11] More recently, Matafonov et al identified that ␤-thrombin and ␥-thrombin, proteolyzed derivatives of ␣-thrombin, also can activate FXI in plasma. 12 The proposal that FXI activation by thrombin plays a significant role in blood clotting in vivo is somewhat controversial.…”
Section: Introductionmentioning
confidence: 99%
“…21 A recent report suggests that FV modestly enhances FXI activation by ␣-IIa. 27 We tested both FV and FVa in the chromogenic substrate assay but saw no evidence for an effect on FXI activation with any type of thrombin.…”
Section: Fxi Activation By Plasma-derived Thrombinmentioning
confidence: 99%
“…21 A recent report suggests that FV modestly enhances FXI activation by ␣-IIa. 27 We tested both FV and FVa in the chromogenic substrate assay but saw no evidence for an effect on FXI activation with any type of thrombin.Previously, we described an FXII-deficient plasma system in which thrombin generation from endogenous prothrombin requires FXI, Ca 2ϩ , and a trigger, such as a small amount of ␣-IIa. 19 Results supported the conclusion that ␣-IIa activates FXI in plasma.…”
mentioning
confidence: 99%
See 1 more Smart Citation